2020
DOI: 10.1007/s10750-020-04423-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of ectoparasite infection in wild-caught and laboratory-bred cichlid fish, and their hybrids, implicate extrinsic rather than intrinsic causes of species differences in infection

Abstract: Parasite-mediated selection may initiate or enhance differentiation between host populations that are exposed to different parasite infections. Variation in infection among populations may result from differences in host ecology (thereby exposure to certain parasites) and/or intrinsic immunological traits. Species of cichlid fish, even when recently diverged, often differ in parasite infection, but the contributions of intrinsic and extrinsic causes are unknown. Here, we compare infection patterns between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…While the parasite faunas of wild-caught fish were found to differ between closely related species, it has been unclear whether this was due to differences in exposure related to habitat use or diet, or to intrinsic differences among species in their vulnerability to parasite taxa. Here Gobbin et al (2020b) explored this issue in Lake Victoria cichlids, comparing the abundance of three ectoparasite taxa (two copepod species and glochidia mussel larvae) on wild and laboratorybred representatives of two closely related species of Pundamilia Seehausen & Bouton, 1998 from Lake Victoria. They found that differences among wild fish did not persist in laboratory stocks.…”
Section: Cichlid Parasitesmentioning
confidence: 99%
“…While the parasite faunas of wild-caught fish were found to differ between closely related species, it has been unclear whether this was due to differences in exposure related to habitat use or diet, or to intrinsic differences among species in their vulnerability to parasite taxa. Here Gobbin et al (2020b) explored this issue in Lake Victoria cichlids, comparing the abundance of three ectoparasite taxa (two copepod species and glochidia mussel larvae) on wild and laboratorybred representatives of two closely related species of Pundamilia Seehausen & Bouton, 1998 from Lake Victoria. They found that differences among wild fish did not persist in laboratory stocks.…”
Section: Cichlid Parasitesmentioning
confidence: 99%